Free Trade Agreement between Tunisia and the European Union, Do Institutions Matter?: An Empirical Validation by A Gravity Model - Kacem, Anis (Journal of Asian Business Strategy, 2015)
Tunisia has signed a free trade agreement with the European Union in 1996, which provides for the reduction of tariff barriers between Tunisia and the EU. In this article, we aim to know and test whether the similarity of the institutional framework has to stimulate international trade between Tunisia and the European Union. In this context, we built a variable called “Institutional distance” to valid the institutional dimension of international trade, near borders effects reported in the literature. To this end, a gravity model was used initially (Tunisia and 21 European countries). Secondly, the estimate shows the existence of spatial autocorrelation. The latter has been corrected using spatial econometrics. The results show that the geographical distance remains more important than the institutions in this type of agreement between north and south shores of the Mediterranean.